(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article should be understood as some sort of prelude to an empirical study that has only just begun. It seeks to explore the perceptions of ethnic-nationally orientated identity constructions of Silesian women living in Southwestern Poland. When it comes to academic disciplines, this essay will touch upon both cultural sociology and regional ethnology. The guiding principle formulated in this essay will initially pursue the current conceptual state within the framework of empirical research, which includes hypothetical assumptions about the aforementioned Silesian women and their identity constructions, while also attempting to gain new insights or refute some of these assumptions. As to systematic research, it becomes clear the topic has been underresearched and the specialised literature is very limited. The situation is similar with the conclusion of this essay, thus only allowing low-threshold conclusions.